The Routledge handbook of translation studies (Routledge, 2013)
The Routledge Handbook of Translation Studies provides a comprehensive, state-of-the-art account of the complex field of translation studies. Written by leading specialists from around the world, this volume brings together authoritative original articles on pressing issues including: the current status of the field and its interdisciplinary nature; the problematic definition of the object of study; the various theoretical frameworks; the research methodologies available